Development of Intelligent Door Lock System for Room Management Using Multi Factor Authentication - Indra Hermawan; Defiana Arnaldy; Prihatin Oktivasari; Dimas Aulia Fachrudin; Risma Nuraini; Nisrina Tsany Sulthanah (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
Keys play an important role in a security system. Most room door security systems still use conventional door locks, especially in room management applications. Room management with conventional keys has several problems, such as long key searches for each loan, and easily lost and duplicated. Therefore, the authors propose a door lock system that is capable of automating room door control and supervision via the internet network. Research that has been done previously uses single factor authentication (SFA). This technology is less secure for the authentication process for parties/users who want to access the room. This research proposes that a system with multi factor authentication (MFA) aims to protect the system from unauthorized users. The MFA concept will be implemented by validating the physical token on the RFID card and the security code or PIN entered by the user. MFA also increases the level of security and allows the implementation of identification, verification and authentication to ensure user authority. The results of this study are system prototypes that can work well, the system can be realized using backend services using expressjs and data stored in cloud services that can be accessed anytime and from anywhere by the client. The system can also be realized using a combination of nodejs, expressjs, PostgreSQL and esp32 client technologies. The validation process at check-in can occur within 207ms. The server is reliable enough to execute 500 requests simultaneously. Overall, the system has worked well for room management.